E-Commerce dan Kelestarian Lingkungan: Analisis Dampak dan Upaya Berkelanjutan - Bima Ramadhani; Agus Hermawan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The rapid development of e-commerce in Indonesia has a significant impact on the growth of the digital economy, but also presents major challenges related to environmental sustainability. This study aims to evaluate the environmental impacts caused by e-commerce activities, especially in terms of increasing plastic waste from single-use packaging, carbon emissions in logistics activities, and energy consumption from data centers. Through a literature study and descriptive analysis approach, this study highlights the large contribution of the e-commerce sector to the volume of domestic waste and the need for effective mitigation strategies. In addition to identifying existing challenges, this study also explores various sustainable practices, such as the use of environmentally friendly packaging, consumer education, and the development of low-emission logistics systems. The results of the study indicate that sustainability in e-commerce can only be achieved through collaboration between the government, business actors, and the community. Strict regulations, technological innovation, and increased consumer awareness are needed so that e-commerce can develop in line with the principles of environmental sustainability.